2013
DOI: 10.3945/ajcn.113.060251
|View full text |Cite
|
Sign up to set email alerts
|

Short-term, high-fat diet increases the expression of key intestinal genes involved in lipoprotein metabolism in healthy men

Abstract: These findings suggest that short-term exposure to a high-fat diet upregulates the expression of key genes involved in lipid and lipoprotein metabolism at the enterocyte level. This trial was registered at clinicaltrials.gov as NCT01806441.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…The study cohort included 221 men covering a wide range of adiposity and glucose homeostasis values. Participants were recruited through the Institute of Nutrition and Functional Food (INAF) clinical unit (Laval University) in the context of several research projects [23][24][25][26][27][28][29][30][31][32][33][34]. Exclusion criteria included smoking, cardiovascular disease, cancer history, monogenic lipid disorder, altered endocrine or hepatic function, gastrointestinal disease, HIV infection, alcoholism and severe dyslipidemia.…”
Section: Study Populationmentioning
confidence: 99%
“…The study cohort included 221 men covering a wide range of adiposity and glucose homeostasis values. Participants were recruited through the Institute of Nutrition and Functional Food (INAF) clinical unit (Laval University) in the context of several research projects [23][24][25][26][27][28][29][30][31][32][33][34]. Exclusion criteria included smoking, cardiovascular disease, cancer history, monogenic lipid disorder, altered endocrine or hepatic function, gastrointestinal disease, HIV infection, alcoholism and severe dyslipidemia.…”
Section: Study Populationmentioning
confidence: 99%
“…Total RNA was then eluted into 100 l RNase-free H 2 O and stored at Ϫ 80°C. RNA quantifi cation and quantitative real-time PCR were performed as described ( 28 ).…”
Section: Total Rna Extraction Rna Quantifi Cation and Quantitative mentioning
confidence: 99%
“…The expression of the housekeeping gene glucose-6-phosphate-dehydrogenase (G6PD) was used as a reference. The intestinal expressions of ACS1 and SAR1B were quantified in n ϭ 95 and n ϭ 84 subjects, respectively, whereas the expressions of SREBP1c, FATP4, FABP2, ACS1, DGAT1, DGAT2, The validity of the intestinal gene expression model used in the present study was demonstrated in previous studies by the interrelationship of the expression of coregulated genes (5,9,10,39,41,42). The validity of the intestinal gene expression model is also supported by positive associations between the expression of the gene and the mass of the protein in biopsy samples, as previously reported (5,42).…”
Section: Methodsmentioning
confidence: 55%
“…The present study is a cross-sectional analysis of data from 127 male subjects who participated in intestinal gene expression studies in our laboratory (5,9,10,39,41,42). These studies were approved by the Laval University Ethical Review Committee, and written consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%